Sengketa Antara Developer Perumahan PT. CIPTA JAYA (Indra Giri Hilir) Dengan Pihak Konsumen dan Kontraktor Perumahan - Riyan Fauma; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
One of the basic human needs is housing, as stipulated in Law Number 1 Year 2011 Article 19 paragraph (1) stating that the organization of houses and housing is done to meet the needs of the house as one of the basic human needs for the improvement and equity of the people's welfare. Housing is one of the basic human needs (BasicNeed) that has existed, along with the human existence itself. The housing medium becomes a means for human beings to perform various life activities and means to provide the ultimate protection against external disturbances, both to climatic conditions and to other disorders.Today building permits have become a major part of building components. This is because almost all forms of licensing require ownership of building permits. For example, to obtain HO (Hinder Ordonantie) permit / improper permit or loan application to a bank, a person must first have a building permitToday the concept of housing has undergone a shift, not only as a basic need and as a medium that gives a sense of calm and peace, but housing has become a life style, giving comfort and showing characteristic or identity which is one pattern of self-development, as well as private means as required by the global communityThe sale-buy binding agreement is basically consensual, because the agreement exists or is born by an agreement by both parties that is the developer and the consumer concerning the making of a buying and selling agreement of the house at a predetermined price.The position of developers (developers) and consumers have the same position / balance in the eyes of the law because it is an affirmation of one of the principles of the rule of law According to Article 2 Law No.8 of 1999 on Consumer Protection that is based on Benefits, Justice, Equilibrium, Security and Safety Consumer, and Legal CertaintyPrinciples and Purposes of Consumer Protection Pursuant to Article 2 of Law No. 8 of 1999 concerning Consumer Protection is based on the Benefit, Justice, Equilibrium, Security and Consumer Safety, and Legal Certainty, described in the Article Article by Article of the Act.In the knowledge of the law of defective whims as contained in Articles 1321- 1328 BW are among others fraud, coercion, and misguidance. According to van Dunne and van der Burght this defect of the will is classic disability defects. Because it always deals with defects in the formation of the will based on the statement of the willKeywords: Dispute –Housing Developer – Consumer- Contractor